Microsurgery Technique in the Foot Reconstruction of Soft Tissue Defects: A Review of 4 Cases - Atmodiwirjo, Parintosa; Sandhi, Afriyanti (Jurnal Plastik Rekonstruksi, 2012)
The restoration of an intact covering is the primary surgical requisite following soft tissue defects in the foot because deep healing can be no better than the surface covering. Soft tissue defects that expose underlying bones, joints, and tendons pose challenging problems and require a free tissue transfer for a successful reconstruction.Total of 4 flaps in the foot was performed between February 2009 to February 2010. We reconstructed soft tissue defects in the foot in 4 patients using 3 free anterolateral thigh (ALT) flaps and 1 free radial forearm (RF) flap. Trauma was the commonest cause in our patients.Free ALT and RF flaps provided stable and durable long-term wound cover in all patients. Complications were few and manageable.Free tissue transfer has become commonplace in many centers around the world. The numerous advantages include stable wound coverage; improve aesthetic and functional outcomes, and minimal donor site morbidity. In our experience, we found that the using of free ALT and RF flaps in foot defects reconstruction, to be technically affordable, reliable and have resulted in excellent outcomes.